Urgensi Dan Strategi Dakwah Santri di Era Digitalisasi - Noval Setiawan; Arifatul khiyaroh (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This article describes the urgency and strategies of students in the digitalization era. In today's digital era, the integration of information and communication technology is one of the challenges of da'wa for students. So it needs to be done by students in order to face technological developments in today's digitalization era. Students should understand digitalization, because social media can be used as a medium for preaching. Today's da'wah is not only through direct face-to-face lectures, but da'wah in this era is widely carried out through social media intermediaries. Attitudes that must be carried out by students in this digital era include: first, being critical of information on social media so that they are not easily swayed into radical understanding. Second, creative attitude in creating da'wah content. This needs to be done so that the existence of social media has a positive impact. Third, promoting good moral and ethical values.The results of the findings of the santri da'wa strategy in the digitalization era include podcasts as a da'wa strategy in the digital era, digitizing Islamic boarding schools books as virtual da'wah and making comics and memes of Islamic da'wa.